Econometric causality - James Joseph Heckman (Institute for the Study of Labor (IZA), 2008)
This paper presents the econometric approach to causal modeling. It is motivated by policy problems. New causal parameters are defined and identified to address specific policy problems. Economists embrace a scientific approach to causality and model the preferences and choices of agents to infer subjective (agent) evaluations as well as objective outcomes. Anticipated and realized subjective and objective outcomes are distinguished. Models for simultaneous causality are developed. The paper contrasts the Neyman-Rubin model of causality with the econometric approach.
urn:nbn:de:101:1-2008040906
Keywords: B41; 330; Causality; econometrics; Roy model; Neyman-Rubin model; subjective and objective evaluations; anticipated vs. realized outcomes; counterfactuals; treatment effects; Kausalanalyse; Ökonometrie; Theorie